The Virus Covid-19 and Dilemmas of Online Technology - Roger Smith (Eco-Vector, 2020)
Commentary on the COVID-19 pandemic must necessarily consider the medical issues in social and political context. This paper discusses one important dimension of the context, the long-term history of human activity as intrinsically technological in its nature. The pandemic has accelerated the use of technology to mediate relations between people at a distance. This involves not only a change in the skills people have (though acquiring these skills has become the central project of work for many people), but changes the sort of person they are. Our notions of closeness and distance, or of touching and being touched, and so on, refer simultaneously to states that are spatial and emotional, factual and evaluative. Inquiry into the differences in human relations where there is physical presence and where there is not raises very significant questions. What are the differences and why are they thought, and felt, to matter? What are the differences when the relationship is supposed to be a therapeutic one? What are the financial and political interests at work in enforcing relations at a distance by new media, i.e., mediated relations? How is a persons agency affected by a lack of freedom to move or a lack of face-to-face contact? What happens to all those human relations for which physical presence was previously the norm, relations such as those performed in the rituals of birth, marriage and death, or in activities like sport and the arts? Can it be said that new technologies involve a loss of soul? The present paper seeks to provide a reflective and open-ended framework for asking such questions.